DESIGN WORK STATION OF PIPE WELDING WITH ERGONOMIC APPROACH - Silvi Ariyanti; Lamto Widodo; Muhammad Zulkarnain; Kevin Timotius (Universitas Mercu Buana, 2019)
The activity of welding specimens on a big pipe that causes various problems for the body, in this activity the worker is at a risky position such as lifting a pipe weight 90 kg, lifting the specimen and welding the pipe with the specimen and the final process is to lower the pipe that has been connected. The purpose of this study is to design workstation by the principles of ergonomics to help reduce physical worker complaints. The research method in this study was the Nordic Body Map (NBM) questionnaire to determine complaints of musculoskeletal disorders (MSDs); the work posture was analyzed by the Rapid Entire Body Assessment (REBA) method. From the results of this study, it can be concluded that the welding work requires a tool in the form of a bench, pipe support, a pulley used at a new welding workstation. With a new workstation, poor work posture can be repaired. With a new work station, there is an efficiency of 8.33 minutes of work time from previous working conditions.